The Degree of Cervical Intervertebral Disc Degeneration Is Associated With Denser Bone Quality of the Cervical Sub‐endplate and Vertebral Body - Jia‐Yu Chen; Jia‐Chen Yang; Ruo‐Yao Li; Zu‐Cheng Huang; Zhi‐Ping Huang; Xiu‐Hua Wu; Qing‐An Zhu; Yin Ding (Orthopaedic Surgery)
ABSTRACT Objective The relationship between cervical disc degeneration and bone quality of adjacent vertebral body remains controversial. This study aims to investigate the relationship between cervical disc degeneration and bone quality of the adjacent vertebral body and sub‐endplate bone with a new MRI‐based bone quality score in patients over 50 years with cervical spondylosis. Methods We retrospectively reviewed 479 cervical disc segments from 131 patients. Disc degeneration at levels C3/C4–C6/C7 was graded using T2‐weighted MRI. Vertebral body quality (VBQ) score and sub‐endplate bone quality (EBQ) score from C3 to C7 were computed from T1‐weighted MRI images. Additionally, bone mineral density (BMD) of the cervical vertebrae was measured in 52 patients using a novel phantom‐less quantitative computed tomography (PL‐QCT) system. The correlation between bone quality score and Pfirrmann grade was analyzed and risk factors for VBQ and EBQ were further evaluated. Results Significant differences were found in cranial VBQ among different Pfirrmann grades, with a score of 2.55 ± 0.54 for Grade 5 discs, which was lower compared to Grades 4 (2.70 ± 0.56) (p < 0.05) and 3 (2.81 ± 0.58) (p < 0.01). Caudal VBQ for Grade 5 discs (2.43 ± 0.52) was also significantly lower than for Grade 3 discs (2.66 ± 0.54) (p < 0.01). EBQ scores decreased with increasing Pfirrmann grades. Negative correlations were observed between both cranial and caudal VBQ and EBQ scores and Pfirrmann grades. Grades 4 and 5 discs were identified as independent risk factors for decreased caudal VBQ and EBQ, whereas only Grade 5 was a significant risk factor for decreased cranial EBQ. Additionally, a moderate correlation (0.4 < R < 0.6, p < 0.05) was noted between vertebral body BMD and VBQ at each cervical level. Conclusion In individuals over 50 years with cervical spondylosis, the severity of disc degeneration was closely correlated with denser bone quality in both the caudal vertebral body and sub‐endplate, as measured by VBQ and EBQ scores. These findings suggest that worsening disc degeneration is associated with increased bone density in specific areas of the cervical spine.